2004
DOI: 10.2527/2004.82113111x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of length of productive life and lifetime prolificacy in the Finnish Landrace and Large White pig populations1

Abstract: The objective of this study was to estimate direct and indirect selection potential for length of productive life and lifetime prolificacy in Finnish Large White and Landrace swine populations. To study the direct selection potential, the heritabilities of these traits were estimated. The genetic correlations of length of productive life and lifetime prolificacy with prolificacy traits and overall leg conformation were estimated to evaluate whether selection for these traits could indirectly improve measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
122
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(166 citation statements)
references
References 7 publications
36
122
7
1
Order By: Relevance
“…Although part of phenotypic correlations might be through an autocorrelation arising from variation in gut fill associated with feed intake, correcting for gut fill has only a minor impact on the estimates. Similar results were observed by Serenius and Stalder (2004) and Bergsma et al (2008). Between-line differences showed that larger maternal size and higher lactation intake also accompanied selection for increased litter size in a mouse model (Rauw et al, 2009), but these associations were not necessarily evident from within-line associations.…”
Section: Discussionsupporting
confidence: 69%
“…Although part of phenotypic correlations might be through an autocorrelation arising from variation in gut fill associated with feed intake, correcting for gut fill has only a minor impact on the estimates. Similar results were observed by Serenius and Stalder (2004) and Bergsma et al (2008). Between-line differences showed that larger maternal size and higher lactation intake also accompanied selection for increased litter size in a mouse model (Rauw et al, 2009), but these associations were not necessarily evident from within-line associations.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, a similar pre-mating phenotype may be arrived at in very different ways, and presumably this has implications for future gilt performance. This potentially explains the relatively poor predictive capacity of absolute finisher and post-finisher performance traits for sow longevity (Tholen et al, 1996b;Serenius and Stalder, 2004) or indeed lactation feed intake (Bunter et al, 2007b) at the phenotypic level, as there are substantial changes to individual sow phenotypes in the intervening period.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlighted the underlying link between leg conformation and both sow productivity and fertility and their influence on sow survivability. It is important to note that leg-conformation scores and specific leg defects did not influence sow survival under the DE-specific competing risk analysis, although the overall influence of leg conformation on sow longevity is well established in the literature (Lopez-Serrano et al, 2000;Serenius and Stalder, 2004;TarrĂ© s et al, 2006a;FernĂ  ndez Competing risk analyses in Duroc sows de Sevilla et al, 2008). It should also be considered that mobility problems would make it more difficult for sows to access resources as well as show a sow's normal behavior under the European Union directive 2001/88/EC (mandatory on European farms from January 1, 2013), which requires farmers to keep sows in group housing, from the 4th week of pregnancy until 1 week before farrowing.…”
mentioning
confidence: 95%
“…Leg and teat conformation Under the general model, overall leg-conformation score influenced sow longevity in LP and LF-specific analyses, as described by Lopez-Serrano et al (2000), Serenius andStalder (2004), TarrĂ© s et al (2006a) and FernĂ  ndez de Sevilla et al (2008) for overall sow survival. Note that longevity records from sows culled due to severe leg-conformation problems were treated as censored in these analyses (less than 20% of sows showed a bad leg conformation after the first and second farrowings), and even so, leg conformation had a relevant influence on LP and LF culling.…”
mentioning
confidence: 99%